2019
DOI: 10.3144/expresspolymlett.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and mechanical properties of dextrin-graft-poly(butyl acrylate-co-styrene) copolymers

Abstract: Dextrin/starch-graft-poly(butyl acrylate-co-styrene) copolymers have been synthesized by radical graft copolymerization and their structure and mechanical properties are reported. High molecular weight grafted chains formation is favored, leading to a low degree of substitution of starch hydroxyl groups. Wide-Angle-X-ray Scattering (WAXS) analysis indicates that all materials are amorphous and Transmission Electron Microscopy (TEM) investigations reveal a two-phase morphology. This is further confirmed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…However, the composite LEBA20 showed diffraction peaks at higher values of 2 theta, several authors which have already reported this kind of diffractograms to attribute the origin of this additional peak to a scattering signal related to the lateral groups of the same size and almost regularly spaced, this agrees with the fact that LEBA20 has the highest BA/St ratio [60], the main amorphous signal located around 20° results from the contribution of both the lignin and the copolymer chains, the disappearance or decrease in intensity of this signals for the intermediate BA/St ratio indicates a loss of this characteristic length, which may suggest that the grafted chains are rather composed of random copolymers.…”
Section: Resultssupporting
confidence: 73%
“…However, the composite LEBA20 showed diffraction peaks at higher values of 2 theta, several authors which have already reported this kind of diffractograms to attribute the origin of this additional peak to a scattering signal related to the lateral groups of the same size and almost regularly spaced, this agrees with the fact that LEBA20 has the highest BA/St ratio [60], the main amorphous signal located around 20° results from the contribution of both the lignin and the copolymer chains, the disappearance or decrease in intensity of this signals for the intermediate BA/St ratio indicates a loss of this characteristic length, which may suggest that the grafted chains are rather composed of random copolymers.…”
Section: Resultssupporting
confidence: 73%
“…Radical and ring-opening functionalizations were first assessed separately. The free radical graft copolymerization of butyl acrylate in water (entry 1) leads to an almost quantitative efficiency, as reported previously (David, 2019). Rather long chains are grafted, with a number-average molecular weight of 80 300 g/mol, and a significant dispersity.…”
Section: Grafting Reactionssupporting
confidence: 71%
“…In particular, the radical graft copolymerization can lead to starch-based materials with interesting properties. In this frame, the synthesis of starch/starch-graft-poly(butyl acrylate-co-styrene) copolymers by free-radical graft polymerization was conducted on native (Meshram, Patil, Mhaske & Thorat, 2009), acetylated (Mou, Li, Wang, Fei & Liu, 2012) starch and dextrin (David et al, 2019). Starch can also be modified by grafting polyesters on its backbone by ring-opening polymerization (ROP) in organic solvents (Chen et al, 2005;Rutot-Houzé et al, 2004) and in water (Choi, Kim & Park, 1999), a tin based catalyst being used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…However, during literature review, we noted that there are fundamental discrepancies in the assignment of signals to dextrin or starch protons. After analyzing the literature describing the 1H NMR studies of oligosaccharides, grafted dextrins, and starch, as well as our research, we assigned the signals essentially according to the proposed method in most published studies in this context [19,20,27,28]. The obtained proton NMR spectra of the dextrin-g-PCL and maltodextrin-g-PCL with proper assignment are presented in Figure 1.…”
Section: Synthesis and Characterization Of Obtained Grafted Dextrin Amentioning
confidence: 99%
“…In the present study, by using the 'graft-from' strategy, we grafted PCL onto the surface of dextrin and maltodextrin by ring-opening polymerization. Thus far, dextrins have been grafted with poly (N-vinyl caprolactam) [19], poly (butyl acrylate-co-styrene) [20], and polylactide [21]. Similar polysaccharide-dextran was grafted with polycaprolactone [22].…”
Section: Introductionmentioning
confidence: 99%